Pekerjaan dan Vokasi Bagi Penyandang Disabilitas dalam Sektor Teknologi Infomasi - Pupu, Ayu; Rahmatrisilvia, Rahmatrisilvia (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the opportunities, challenges, and strategies for empowering persons with disabilities in accessing employment and career development in the field of information technology. The method used is a descriptive study based on a literature review of 20 reputable international journal articles published between 2018 and 2025. The analysis process was carried out by identifying the main themes related to the use of information technology, the forms of support available, and the structural barriers faced by persons with disabilities in the world of work. The results of the study show that information technology plays a significant role in expanding employment opportunities, increasing independence, and strengthening the career prospects of persons with disabilities through the use of assistive technology, digitisation of the work environment, information and communication technology-based training, and skills development through metaverse technology. However, this study also found a number of key challenges, including limited access to technology, high costs of assistive devices, low levels of digital system accessibility, and digital skill gaps. This study concludes that the sustainable empowerment of persons with disabilities requires the development of an inclusive technology ecosystem through collaboration between the government, educational institutions, the business world, technology providers, and organisations for persons with disabilities.